Breeding and utilization of recessive genic male sterile line LY31AB in Brassica napus L. - XU Mingchao; HUANG Qian; ZHANG Kangni; ZOU Xudong; CHEN Xingfan; LU Hong; WANG Yanhui; ZHANG Zhi (浙江大学学报. 农业与生命科学版)
In order to make full use of the advantages of genic male sterility (GMS), the commercial rapeseed ‘Q1012’ of Brassica napus L. was used as the source to select the double-low and high-quality recessive GMS line LY31AB of B. napus by the pedigree breeding method. LY31AB fertility, resistance, combining ability and other characteristics were analyzed and its heterosis was utilized. The results indicated that the sterility of LY31AB was genetically stable, which was controlled by two pairs of recessive overlapping genes, and showed good resistance to sclerotinia disease and lodging resistance in the field. LY31AB had high combining ability, wide recovery sources and strong heterosis, and most of its combinations showed obvious heterosis. Four new double-low and high-quality rape varieties, Leyou 8, Deleyou 1632, Wanjiayou 520 and Leyou 7, which were bred using LY31AB and registered, also showed good resistance to sclerotinia disease and lodging resistance, and were widely in promotion and application. To sum up, LY31AB is a sterile line with clear pedigree, stable genetic characters, good quality, good fertility, good resistance, high combining ability, wide recovery sources and good heterosis utilization value, and has broad application prospects.